Mapping the Discourse of Power: Diplomatic Actors on X (Formerly Twitter) - Oloo, Daniel (LSPR Institute of Communication & Business, 2025)
This study explored the impact of power dynamics on digital diplomacy by analyzing the Twitter usage of three diplomatic actors (the Chinese, UK, and US Embassies in Kenya). The research aimed to answer questions about who the diplomats prioritized for engagement, how they used Twitter in crisis communication, and how they became media actors by adopting media logic in their digital diplomacy practices. The results of the study showed that Twitter was utilized by diplomats to control the daily agenda, express opinions, and influence followers and media outlets. The Chinese and UK Embassies made use of the platform for formal communication and to communicate with their diaspora. The US ambassador followed online influencers to set the online conversations and expand their online presence. Meanwhile, the UK ambassador leveraged the media to drive foreign policy and tailor messages to the Kenyan audience. The findings also indicated that all embassies had adopted a media logic by following various media sources. The study also found that the Chinese embassy was quick to respond to any tweet that mentioned human rights issues in Xinjiang, Tibet, and Inner Mongolia, and used Twitter as a tool to correct misinformation. In conclusion, diplomats use Twitter as a tool to engage with different audiences and achieve their diplomatic goals through interactive strategies such as two-way communication, storytelling, influencer engagement, hashtag campaigns, and media amplification. However, diplomats need to constructively engage with the digital public to accomplish their goals, while avoiding the risk of their messages being misconstrued.